Possibility of Taking an Offensive Stance in Extravasation Injury: Effects of Fat Injection in Vesicant (Doxorubicin) Induced Skin Necrosis Model in Rats. Issue 4 (3rd April 2022) - Bicer, Ahmet; Ercin, Burak Sercan; Gürler, Tahir; Yiğittürk, Gürkan; Uyanikgil, Yigit; Cetin, Emel Oyku
Abstract: Introduction: Extravasation injuries are one of the most feared complications of intravenous drug administration. The most common drugs associated with extravasation injury include chemotherapy agents and contrast media. Natural course of vesicant extravasation is discomfort, pain, swelling, inflammation, and ultimately skin ulceration. While diligence is the principle approach in prevention, immediate bed-side measures are as important in controlling the extent of tissue damage. Various options, either medical or interventional are next steps in treatment of the condition including antidotes, volume dilution, flushing, suction, hyperbaric oxygen therapy, and surgery. Materials and methods: 12 male Wistar albino rats were divided into two groups; one group received fat injections following subdermal doxorubicin infiltration in their right thighs, while other group received saline injection following subdermal doxorubicin infiltration in their right thighs for dilution. Left thighs of both groups were left untreated following subdermal doxorubicin infiltration. Total area of necrosis, as well as resultant epidermal thicknesses were assessed. Histological analyses were conducted using modified Verhofstad scoring system for comparison. Results: Mean necrotic area was significantly smaller in the fat injection group compared to other groups. Median Verhofstad score was lesser in the fat injection group as well. Median epidermal thickness, on the other hand, was greater in the fat injection group. Conclusion: Injection of fat grafts following vesicant extravasation might be beneficial in preventing the progression of tissue damage, if employed early.